Comparative effect of biochar and activated carbon addition on the mesophilic anaerobic digestion of piggery waste in batch mode. Issue 9 (29th July 2021) - Herrmann, Christiane; Sánchez, Enrique; Schultze, Maja; Borja, Rafael
Abstract: A comparative study of the batch mesophilic anaerobic digestion of piggery waste was carried out with the addition of 5% biochar and 5% activated carbon. The results obtained showed that the bioreactors amended with biochar increased cumulative methane production, the kinetic constant for methane production and the COD removal efficiency compared to the control reactors and reactors with activated carbon addition. The maximum methane production and the kinetic constant were 6.9% higher in the reactors with biochar addition compared to the controls; while the COD removal efficiency was 3% higher in the case of biochar addition. In the case of activated carbon, only a slight improvement in anaerobic digestion performance was observed compared to the control.